2020
DOI: 10.1101/2020.02.27.968891
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cellular and structural basis of synthesis of the unique intermediate dehydro-F420-0 in mycobacteria

Abstract: 28F420 is a low-potential redox cofactor used by diverse bacteria and archaea. In mycobacteria, 29 this cofactor has multiple roles, including adaptation to redox stress, cell wall biosynthesis, and 30 activation of the clinical antitubercular prodrugs pretomanid and delamanid. A recent 31 biochemical study proposed a revised biosynthesis pathway for F420 in mycobacteria; it was 32 suggested that phosphoenolpyruvate served as a metabolic precursor for this pathway, rather 33 than 2-phospholactate as long pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Vitamin B6 is essential for the survival and virulence of M. tuberculosis [ 68 ] and its cofactor (F420-dependent biliverdin reductase) is implicated in immune-evasive mechanisms to allow bacterial persistence [ 66, 67 ] (Table S3). Recently, it has been reported that the synthesis of F420 might be stimulated by phosphoenolpyruvate [ 69 ], which is the precursor to pyruvate, a supplement often added to culture medium to improve the in vitro growth of L5, L6 and M. bovis strains. Furthermore, there is a suggestion that F420 is needed for the activation of the antituberculosis drugs pretomanid and delamanid [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin B6 is essential for the survival and virulence of M. tuberculosis [ 68 ] and its cofactor (F420-dependent biliverdin reductase) is implicated in immune-evasive mechanisms to allow bacterial persistence [ 66, 67 ] (Table S3). Recently, it has been reported that the synthesis of F420 might be stimulated by phosphoenolpyruvate [ 69 ], which is the precursor to pyruvate, a supplement often added to culture medium to improve the in vitro growth of L5, L6 and M. bovis strains. Furthermore, there is a suggestion that F420 is needed for the activation of the antituberculosis drugs pretomanid and delamanid [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that the synthesis of F420 might be stimulated by phosphoenolpyruvate [ 69 ], which is the precursor to pyruvate, a supplement often added to culture medium to improve the in vitro growth of L5, L6 and M. bovis strains. Furthermore, there is a suggestion that F420 is needed for the activation of the antituberculosis drugs pretomanid and delamanid [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…All analyses for these were performed using GraphPad Prism 9 with a statistical significance established at p <0.05. FbiC, FbiB and FbiA, 5-A-RU can also be converted to F420 (62). DMRL and its derivatives can act as MAIT cell activators.…”
Section: Relative Quantification Of Rf Pathway Proteins By Mrm-msmentioning
confidence: 99%
“…Vitamin B6 is essential for survival and virulence of M. tuberculosis (Dick et al 2010) and its cofactor (F420 dependent biliverdin reductase) is implicated in immune-evasive mechanisms to allow bacterial persistence (Ahmed et al 2016;Selengut and Haft 2010) (Table S6). Recently, it has been reported that the synthesis of F420 might be stimulated by phosphoenolpyruvate (Grinter et al 2020), which is the precursor to pyruvate, a supplement often added to culture medium to improve the in vitro growth of L5, L6 and M. bovis. Furthermore, there is a suggestion that F420 is needed for the activation of the antituberculosis drugs pretomanid and delamanid (Grinter et al 2020).…”
Section: The Classification Of the L5-specific Genes Into Functional mentioning
confidence: 99%
“…Recently, it has been reported that the synthesis of F420 might be stimulated by phosphoenolpyruvate (Grinter et al 2020), which is the precursor to pyruvate, a supplement often added to culture medium to improve the in vitro growth of L5, L6 and M. bovis. Furthermore, there is a suggestion that F420 is needed for the activation of the antituberculosis drugs pretomanid and delamanid (Grinter et al 2020).…”
Section: The Classification Of the L5-specific Genes Into Functional mentioning
confidence: 99%